FILSAFAT, ETIKA DAN ILMU: Upaya Memahami Hakikat Ilmu dalam Konteks Keindonesiaan - Wilujeng, Sri Rahayu (HUMANIKA, 2013)
ABSTRACT Philosophy emerged in the Greek region about two thousand five hundred years ago as an effort to seek the truth. This is an important moment for the birth of science. Philosophy is the mother of science. Science is essentially an attempt to help human solve the problem. Science should benefit humansâ€™ life. However, due to the development of science is very rapid paradigm change, not more science to human, but human for the sciences. Science separated from its ethical dimension, so that science became lost itâ€™s substantially. Francis Bacon motto that knowledge is power has led to the loss of Sciences essentially, in turn, will lead to the destruction and human misery. Keywords: philosophy, ethics, science, humanÂ